Estimation of the influence of hypoglycemia and body mass index on health-related quality of life, in patients with type 2 diabetes mellitus - Cvetanović, Goran Z; Stojiljković, Marija; Miljković, Mirjana (Vojnosanitetski pregled, 2017)
Background/Aim. Recent data have shown that obese patients with type 2 diabetes mellitus (T2DM) have more commonly impaired glycemic control and complication such as neuropathy as well as a higher mortality rate than normal body weight patients with diabetes. The aim of this study was to quantify patient-reported rates of hypoglycemia, determine body mass index (BMI) and evaluate their association with health-related quality of life (HRQL) estimated by EuroQoL-EQ 5-dimensional (EQ-5D) questionnaire in individuals with T2DM after adjusting for age, duration of diabetes mellitus and presence of late diabetes complications. Methods. This clinical-epidemiological cross sectional study involved 269 consecutively selected adult patients of both sexes with T2DM duration longer than one year. The standardized Serbian version of the EQ-5D 3 level version – EQ-5D-3L questionnaire with a visual analogue scale-VAS (EQ-VAS), was used to assess respondents’ HRQL and utility values. Results. The average age of participants was 65.1 ± 9.3 years; hypoglycemia was registered in 71.0%, obesity in 43.9% and chronic complications in 88.8% of the patients. Half of the patients did not reach the target value of glycated hemoglobin (HbA1c)
Keywords: diabetes mellitus; type 2; quality of life; hypoglycemia; body mass index